Surrogate Spike Train Generation Through Dithering in Operational Time - Louis, Sebastien G.; Gerstein, george L.; Gruen, sonja; Diesmann, Markus (Frontiers in Computational Neuroscience, 2010)
Detecting the excess of spike synchrony and testing its significance can not be done analytically in many types of spike trains and relies on adequate surrogate methods. The main challenge for these methods is to conserve certain features of the spike trains, the two most important being the firing rate and the inter-spike interval statistics. In this study we make use of operational time to introduce generalizations to spike dithering and propose two novel surrogate methods which conserve both features with high accuracy. Compared to earlier approaches, the methods show an improved robustness in detecting excess synchrony between spike trains.